Power Tariffs : Caught between Cost Recovery and Affordability - Briceno-Garmendia, Cecilia; Shkaratan, Maria (2012)
This is the first paper to build a comprehensive empirical picture of power pricing practices across Sub-Saharan Africa, based on a new database of tariff structures in 27 countries for the years 2004-2008. Using a variety of quantitative indicators, the paper evaluates the performance of electricity tariffs against four key policy objectives: recovery of historic power production costs, efficient signaling of future power production costs, affordability to low income households, and distributional equity. As regards cost recovery, 80 percent of the countries in the sample fully recover operating costs, while only around 30 percent of the countries are practicing full recovery of capital costs. However, due to the fact that future power development may be based on a shift toward more economic technologies than those available in the past, existing tariffs look as though they would be consistent with Long Run Marginal Costs in nearly 40 percent of countries and hence provide efficient pricing signals. As regards affordability, today's average effective tariffs are affordable for 90 percent of today's customers. However, they would only be affordable for 25 percent of households that remain unconnected to the grid. Tariffs consistent with full recovery of economic costs would be affordable for 70 percent of the population. As regards equity, the highly regressive patterns of access to power services, ensure that subsidies delivered through electricity tariffs are without exception also highly regressive in distributional incidence. The conclusion is that achieving all four of these policy objectives simultaneously is almost impossible in the context of the high-cost low-income environment that characterizes much of SSA today. Hence most countries find themselves caught between cost recovery and affordability.